Proaktivnosti in terensko delo v izobraževanju za trajnostni razvoj - Kolnik, Karmen (Revija za geografijo, 2007)
A global develpment stategy of UNESCO is to integrate the principles, values and practice of sustalnab/e developemenf into all aspects of lifelong education. We are talking of the need that every economical and social development and protection of the environment has to work connected and in harmony, and in this aspect the education is playing a big part. Proactivity in education includes taking into account needs of the future, which are based on the development of values and space relations, which are responsible to the needs of future generations. The integration roll of geograpy as social and natual orientated science is an important interdistiplinary foundation for education for sustainable development. Geography, particularly geographical fieldwork, has a special and irreplaceable role in regard to promotion and development of critical thinking, problem solving and proposing behavioural changes.
Keywords: ecology; education; ekologija; izobraževanje; sustainable development; terensko delo; trajnostni razvoj